1997
DOI: 10.1002/(sici)1097-4644(19970615)65:4<527::aid-jcb8>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rad's effector-binding domain, intracellular localization, and analysis of expression in Pima Indians

Abstract: In order to characterize the endogenous gene product for rad (ras-related protein associated with diabetes), we prepared antibodies to synthetic peptides that correspond to amino acids (109-121, 178-195, 254-271) within the protein. These antibodies were used to analyze the expression, structure, and function of rad. Western analysis with these antibodies revealed that rad was a 46 kDa protein which was expressed during myotube formation. Further, immunolocalization studies showed that rad localized to thin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…Rad (Ras Associated with Diabetes) is a 35-kDa GTPase that was identified by subtractive cloning as overexpressed in skeletal muscle of patients with type 2 diabetes mellitus (1,2). Although some subsequent studies (3,4) did not confirm this direct association between the Rad mRNA level and diabetes, other studies have shown that Rad is an insulin regulated gene in muscle (5) and that Rad overexpression inhibits glucose transport in muscle cells in culture (6). There is also a correlation between the level of Rad expression and obesity (3), and genetic analysis studies of two different populations found a possible association between trinucleotide-repeat polymorphism of the Rad gene and type 2 diabetes (7,8).…”
contrasting
confidence: 59%
“…Rad (Ras Associated with Diabetes) is a 35-kDa GTPase that was identified by subtractive cloning as overexpressed in skeletal muscle of patients with type 2 diabetes mellitus (1,2). Although some subsequent studies (3,4) did not confirm this direct association between the Rad mRNA level and diabetes, other studies have shown that Rad is an insulin regulated gene in muscle (5) and that Rad overexpression inhibits glucose transport in muscle cells in culture (6). There is also a correlation between the level of Rad expression and obesity (3), and genetic analysis studies of two different populations found a possible association between trinucleotide-repeat polymorphism of the Rad gene and type 2 diabetes (7,8).…”
contrasting
confidence: 59%
“…Rem is expressed predominantly in cardiac muscle, but also at more modest levels in lung, kidney, and skeletal muscle [3]; Rem2 is highly expressed in the brain and kidney, but also in neuroendocrine tissues [4]; Rad is found in abundance in cardiac and skeletal muscle [6]; while Gem/Kir is found in a diverse set of tissues, including myeloid cells, kidney, liver, and lung [5]. Rad was initially identified as a gene overexpressed in the skeletal muscle of non-insulin dependent diabetics [6], though subsequent studies in Pima Indians and the Zucker diabetic rat model imply that this effect is not universal [39]. Regulation may result from the hyperinsulinemia associated with the disease [40] as insulin has been shown to increase Rad mRNA levels in muscle [25].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…32 Although an association between Rad upregulation and type 2 diabetes mellitus could not be confirmed, a correlation with obesity was reported. 33 It was also reported that Rad inhibits insulin-stimulated glucose uptake in myocyte and adipocyte cell lines. 7 A recent report revealed that Rad is highly expressed in a breast cancer cell line with high tumorigenic and metastatic potential, promoting growth and accelerating cell cycle transition.…”
Section: Chang Et Al Role Of Rad In Cardiac Hypertrophy 2981mentioning
confidence: 99%